การวิเคราะห์การเผาไหม้และภาพปรากฏการณ์การเผาไหม้ของเชื้อเพลิง DME ในเครื่องยนต์ดีเซลชนิดห้องเผาไหม้ล่วงหน้า - อัคฆพงศ์ สถาวรินทุ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To study DME combustion characteristics, using heat release analysis and visualization technique, in an IDI CI engine. The work was divided into three parts. First, engine performance study with DME fuelled. Second, engine combustion characteristic studies using heat release analysis. Third, engine combustion images studies by means of engine visualization. Results from a full load engine performance test shows that engine’s maximum brake torque and energy conversion efficiency will be increased when engine compression ratio has been reduced from OEM’s standard (21:1) to 16.1:1. The maximum engine’s brake torque at engine speed of 1000 rpm is 12.04 Nm with fuel injection timing of 24 degree BTDC and at engine speed 1200 rpm and 1400 rpm is 11.56 Nm with fuel injection timing of 26 degree BTDC. However, engine’s energy conversion efficiency will be maximized with fuel injection timing of 28 degree BTDC at all engine speeds. The results from part load engine performance test also show that engine’s energy conversion efficiency will be maximized with fuel injection timing of 28 degree BTDC at all test point. Exhaust black smoke was not found at all engine test conditions. Results of engine combustion characteristic studies reveal that the more the advance of engine fuel injection timing, the higher the maximum in-cylinder pressure. The highest mass fraction burned will be occurred with fuel injection timing of 28 degree BTDC. The engine’s combustion visualization with flash on shows that injected fuel from nozzle hole could be observed at 15-20 CA after the SOI. The fuel’s spray penetration is short due to the sudden vaporized of DME, then mix with air and suddenly burn. The demand of latent heat of DME vaporization during its phase change results in lower engine combustion chamber’s temperature thus spray liquid core can be observed. Combustion images without flash on show that the flame can be observed since the SOI. DME combustion has blue flame due to its low amount of soot in flame. Therefore, diesel like luminous flame cannot be seen. Finally, this research can be concluded that DME fuel is a clean alternative fuel for pollution reduction. For the best use of engine’s model that is employed in this work, the optimum energy conversion efficiency and mass fraction burned can be achieved when its compression ratio is reduced to 16.1:1 and engine fuel injection timing is adjusted to 28 degree BTDC.